State of the art of bulk-fill resin-based composites: a review - Camila Corral-Núñez; Patricio Vildósola-Grez; Cristian Bersezio-Miranda; Edson Alves-Dos Campos; Eduardo Fernández-Godoy (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Bulk-fill resin-based composites (RBCs) have recently been introduced on the market, and according to the manufacturers, they could be used to restore cavities in 4- or 5-mm thick increments. This would probably mean a major technique simplification compared to the incremental technique. However, the properties and modes of use of RBCs vary significantly between one and the other. In addition, due to their recent appearance on the market, there are not enough studies that validate the clinical performance of these materials. This article aims to conduct a state of the art review of the available literature on the Medline/Pubmed and ScIELO databases, published between 2000 and 2014, describing the composition, classification, and results of studies currently published.